Assessment of the efficiency of traditional earthquake resistant techniques for vernacular architecture. (15th October 2018) - Ortega, Javier; Vasconcelos, Graça; Rodrigues, Hugo; Correia, Mariana
Highlights: The earthquake resistant techniques evaluated are result of a local seismic culture. The techniques were evaluated using numerical modeling and pushover analyses. All techniques were confirmed to affect the seismic behavior of vernacular buildings. The different techniques were compared among them in quantitative terms. The structural improvement obtained with the use of each technique was highlighted. Abstract: Specific architectural elements can be identified in constructions located in regions frequently exposed to earthquakes. These earthquake resistant features were developed empirically by local communities to protect their built-up environment. Research in these traditional practices, resulting from a local seismic culture, is a relevant and positive approach, since it focuses on the strength of the system rather than on its weaknesses. Its integration into current vernacular building practices can help to preserve and retrofit surviving in-use examples while respecting their authenticity. The main goal of the present work is to assess numerically the efficiency of traditional earthquake resistant solutions to mitigate the seismic vulnerability of vernacular architecture. The paper thus presents the results of a detailed numerical study based on finite element modeling and nonlinear static (pushover) analysis intended to quantitatively evaluate the influence of each technique on the seismic behavior of vernacular constructions and to better understand their structural role under seismic loading.